2008
DOI: 10.1037/0033-2909.134.2.301
|View full text |Cite
|
Sign up to set email alerts
|

Methamphetamine abuse and impairment of social functioning: A review of the underlying neurophysiological causes and behavioral implications.

Abstract: The highly addictive drug methamphetamine has been associated with impairments in social cognitions as evidenced by changes in users' behaviors. Physiological changes in brain structure and functioning, particularly in the frontal lobe, have also been identified. The authors propose a biopsychosocial approach to understanding the effects of methamphetamine addiction by relating the physiological effects of the drug to the behaviors and social cognitions of its users, through the application of the theory of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
164
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 256 publications
(174 citation statements)
references
References 106 publications
4
164
0
2
Order By: Relevance
“…Given that social-cognitive abilities have been shown to be key factors in the development, progress, and prognosis of other psychiatric conditions such as schizophrenia [16], it was analogously suggested that social cognition and interaction may likewise play a crucial role in the origin and course of stimulant use disorders [17,18]. Accordingly, deficits in social cognition and behaviour may increase social isolation, aggression, and depression, predictably preserving the vicious circle of drug addiction [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given that social-cognitive abilities have been shown to be key factors in the development, progress, and prognosis of other psychiatric conditions such as schizophrenia [16], it was analogously suggested that social cognition and interaction may likewise play a crucial role in the origin and course of stimulant use disorders [17,18]. Accordingly, deficits in social cognition and behaviour may increase social isolation, aggression, and depression, predictably preserving the vicious circle of drug addiction [17].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, deficits in social cognition and behaviour may increase social isolation, aggression, and depression, predictably preserving the vicious circle of drug addiction [17]. Moreover, it has been suggested that repeated stimulant intake impacts the fronto-striatal reward system by enhancing the value of the drug of abuse, while simultaneously reducing the sensitivity for the rewarding nature of social contacts [18].…”
Section: Introductionmentioning
confidence: 99%
“…However, neural substrates that are responsible for emotion recognition are also involved in drug addiction(Verdejo-García and Bechara, 2009)and thus they were found to be impaired (Rosselli and Ardila, 1996;Reay et al, 2006;Homer et al, 2008).To the best of our knoweledge, the relationship between heroin addiction and emotion recognition has not been studied, but a lot of work has been conducted on other illicit drugs such as alcohol (Frigerio et al, 2002), polysubstance abuse (Foisy et al, 2005;Fernández-Serrano et al, 2010), opiates (Kornreich et al, 2003), cocaine (Kemmis et al, 2007) and psychostimulants (Verdejo-García et al, 2007a). The most consistent finding was the abnormal recognition of negative emotions that is independent of abstinence length (Fernández-Serrano et al, 2010).Abstinent PSA showed poorer facial recognition of anger, fear and disgust and sadness, despite the length of abstinence but no significant difference was found in recognition of neutral or positive emotions, including surprise and happiness, relative to the control group (Fernández-Serrano et al, 2010).…”
Section: Abnormal Resting-state Topological Properties In Heroin-depementioning
confidence: 99%
“…In other words, a network member observing the substance use by the other members has the tendency to mimic the friends' behavior (Reifman et al, 2006;Bohnert et al, 2009) Emotion recognition is essential to social readjustment and interaction (Blair, 2003;Fernández-Serrano et al, 2010). However, neural substrates that are responsible for emotion recognition are also involved in drug addiction(Verdejo-García and Bechara, 2009)and thus they were found to be impaired (Rosselli and Ardila, 1996;Reay et al, 2006;Homer et al, 2008).To the best of our knoweledge, the relationship between heroin addiction and emotion recognition has not been studied, but a lot of work has been conducted on other illicit drugs such as prefrontal GM volumeatrophy and frontal WM deficits might be a biomarker for behavioral and neuropsychological deregulations underlying heroin addiction (Lyoo et al, 2006;Li et al, 2013c;Zhang et al, 2013). However, the reversibility in GM alterations might provide an explanation for the recovery of several cognitive skills andanxiety .…”
mentioning
confidence: 99%
“…Its acute administration is associated with euphoria, increased attention, and increased physical activity [17,33]. Chronic METH abuse is complicated by addiction, depression, and psychosis [8,29,32].…”
Section: Introductionmentioning
confidence: 99%